Impact of counseling on cervical cancer and its screening on women knowledge, health beliefs and protective practices - HosseAbedelAzim Mohamedin, Hoda; El-sayed Hossein, Yosria (International Journal of Advanced Nursing Studies, 2018)
Background: Cervical cancer can be preventable or detected early especially with a series of regular screening with Pap tests.Aim of the study: The aim of this study were to evaluate the impact of counseling on cervical cancer and its screening on women knowledge, health beliefs and protective practices.Subjects and Methods: A quasi-experimental design was used. A convenient ample of 120 women were randomly divided into experimental and control groups, each group consisted of 60 women were recruited from outpatient clinic at Obstetrics and Gynecology Department at Minia General Hospital.Results It can be observed that, 86% of the women in the intervention group had good knowledge compared to only 17% of the control group and the difference is statistically significant. The mean score of perceived susceptibility and barriers in both groups was reduced but the decrease was significantly higher in the intervention group (P
Keywords: Cervical Cancer; Health Beliefs; Pap smear test.